Proton-coupled electron transfer controls peroxide activation initiated by a solid-water interface - Jian-Hua Chen; Wan-Ting Li; Kun-Yu Cai; Hui-Jie Tu; Zi-Tong Long; Shoaib Akhtar; Lin-Dong Liu (Nature Communications)
Abstract Decentralized water treatment technologies, designed to align with the specific characteristics of the water source and the requirements of the user, are gaining prominence due to their cost and energy-saving advantages over traditional centralized systems. The application of chemical water treatment via heterogeneous advanced oxidation processes using peroxide (O–O) represents a potentially attractive treatment option. These processes serve to initiate redox processes at the solid-water interface. Nevertheless, the oxidation mechanism exemplified by the typical Fenton-like persulfate-based heterogeneous oxidation, in which electron transfer dominates, is almost universally accepted. Here, we present experimental results that challenge this view. At the solid-liquid interface, it is demonstrated that protons are thermodynamically coupled to electrons. In situ quantitative titration provides direct experimental evidence that the coupling ratio of protons to transferred electrons is almost 1:1. Comprehensive thermodynamic analyses further demonstrate that a net proton-coupled electron transfer occurs, with both protons and electrons entering the redox cycle. These findings will inform future developments in O–O activation technologies, enabling more efficient redox activity via the tight coupling of protons and electrons.